Visibility analysis of Medieval and Early Modern period fire beacon sites in Turku Archipelago, Southwestern Finland - Saunaluoma, Sanna; Leppänen, Jere (Suomen arkeologinen seura ry, 2025)
A defense and guarding system consisting of fire beacon networks was commonly used in Scandinavian coastal areas from the Late Iron Age until the Early Modern period. A chain-like system of signal fire stations was established in locations strategically important for defense and activated if the threat of an enemy attack concretized. Historical sources evidence that the same defense system was also utilized in the archipelago and coastline of southern Finland. Also, certain place names are considered to reflect ancient warning fire activities. Using GIS-based analyses, we examine whether these place names in the Turku archipelago can be distinguished from other locations based on their visibility and topography. In addition, we investigate how visible other potential signal fire stations and certain sailing routes are from the sites selected for the analysis, and the possibility of them having an interactive connection based on visual observation.